Introducing social evaluation for improved project performance : a suggested checklist approach. - Fernandes, A.J. (1990)
Identifies five social dimensions of project evaluation which require special attention : organizational capacity; level of enlightenment of target group; social and power relations within the group; demographic and human development in the catchment area; and, health status.